2015
DOI: 10.1007/s00431-015-2535-3
|View full text |Cite
|
Sign up to set email alerts
|

The utility of bioimpedance analysis for monitoring the children with nutcracker syndrome

Abstract: • Nutcracker syndrome (NCS) is very rare and characterized by the compression of LRV between aorta and SMA. What is new: • Patients with NCS have a slimmer body feature with lower anthropometric and BIA indices. • Fat percentage indicates the degree of LRV entrapment and amount of proteinuria in NCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Some researchers (Nielsen, Stephen, Freedland, & Jarow, 2006;Umul et al, 2016) have proposed a possible mechanism that the increased adipose tissue could provide a cushion protecting against the nutcracker phenomenon and protect the left renal vein from compression in the obese men. Yavuz, Kıyak, Er, and Korkmaz (2015) demonstrated that weight, BMI and body fat rate were significantly lower in nutcracker phenomenon patients than in controls. Based on the current available literature mentioned above, the results of our meta-analysis do confirm this concept that adiposity protects against varicocele.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some researchers (Nielsen, Stephen, Freedland, & Jarow, 2006;Umul et al, 2016) have proposed a possible mechanism that the increased adipose tissue could provide a cushion protecting against the nutcracker phenomenon and protect the left renal vein from compression in the obese men. Yavuz, Kıyak, Er, and Korkmaz (2015) demonstrated that weight, BMI and body fat rate were significantly lower in nutcracker phenomenon patients than in controls. Based on the current available literature mentioned above, the results of our meta-analysis do confirm this concept that adiposity protects against varicocele.…”
Section: Discussionmentioning
confidence: 92%
“…This theory states that varicocele arises from mainly an elevated blood pressure of the left renal vein because it is influenced by the compression of the superior mesenteric artery and the aorta (Handel et al, 2006;Philip, Robeva, & Analia, 2008). Yavuz, Kıyak, Er, and Korkmaz (2015) demonstrated that weight, BMI and body fat rate were significantly lower in nutcracker phenomenon patients than in controls. Yavuz, Kıyak, Er, and Korkmaz (2015) demonstrated that weight, BMI and body fat rate were significantly lower in nutcracker phenomenon patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] LRV hypertension-related clinical symptoms are diverse and non-specific. 2,3,6,12 However, exacerbation by the long period of standing and walking is remarkable. 3,4,13 In retrospect our patient also had recurrent admissions with abdominal pain triggered by physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The patients had slimmer body, with lower bioimpedance measures. It was suggested to restore the aortomesenteric fat tissue with nutrition, which may resolve the left renal vein entrapment (25).…”
Section: Nephrourological Evaluationmentioning
confidence: 99%